The Development of Teaching Materials on Integrated Science, Technology, and Religion to Improve College Students’ Integrative Knowledge - Muhammad Nasir; Hadma Yuliani; Luvia Ranggi Nastiti (Institut Agama Islam Negeri Imam Bonjol Padang, 2019)
The purposes of this study were (1) to determine the specifications of teaching materials integrated STR; and (2) to analyze the results of expert validation to teaching materials integrated STR. The research method used in this study was Research and Development (R D) with a four-D procedure (Define, Design, Develop, and Disseminate). The data analysis technique used was descriptive analysis techniques. The results of the study show that (1) The profile of the teaching materials integrated STR are (a) teaching materials are integration between concepts of fundamental of physics and Islamic values of Al-Quran and Hadith ; and (b) the media developed is an integration between PPT and Phet; and (2) The results of the material expert validation on the results of the development of teaching materials integrated STR on aspects of content feasibility, aspects of presentation, aspects of language, and material integration are well categorized. Likewise, the results of media expert validation on the display and programming aspects show good categories